Pola Asuh Orang Tua Dalam Mengatasi Perilaku Sibling Rivarly Pada Anak Usia Dini - Raden Rachmy Diana; Id’ha Tutfi Ulkhatiata (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2023)
Sibling rivarly is a competitive behavior between siblings that can cause jealousy in children, in overcoming it, parents must have basic knowledge about this behavior, so this study aims to describe how parents' pola asuhes in dealing with sibling rivarly behavior. This research is a type of qualitative-descriptive research based on post-positivism philosophy, with research subjects of three families having two or more children with an age limit of 0-6 years. Based on the results of this study, of the 3 subjects, there were 2 families who had the same handling strategy, namely from the start they had instilled knowledge to always get along with fellow siblings, to be fair, not to compare children but there was also one subject that needed to be improved in using pola asuhes to deal with behavior sibling rivarly.